Functional MRI Study of Language Dominance - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Functional magnetic resonance imaging (fMRI) was used to determine the pattern of receptive language lateralization in 11 healthy children (7 girls, 4 boys; mean age, 8.5 yrs) at Children's National Medical Center, George Washington School of Medicine, DC.